MANAJEMEN SATGAS PASIEN COVID (PENGGUNAAN APD) DI RUMAH SEHAT APARMA UNIPDU - Kurniawati Kurniawati; Zuliani Zuliani; Ana Farida Ulfa; Pujiani Pujiani; Masruroh Masruroh; Abdul Ghofar; Siti Muniroh; Zulfikar Zulfikar; Wim Banu Ukhrowi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The condition of the spread of Covid-19 has reached almost the entire world with the number of cases continuing to increase. Health workers act as service providers, therefore hospitals have an obligation to nourish their workforce. There are ways to overcome and reduce the possibility of work accidents and occupational diseases (PAK). One of them is by increasing the frequency of using personal protective equipment (PPE). PPE only functions to reduce contact with hazards by placing a barrier between workers and the dangers that exist in patients and vice versa. Purpose: To analyze the influence of the variables Availability of Personal Protective Equipment (PPE) and Education on nurse job satisfaction. Method: Descriptive in nature, namely a research design that is directed to describe symptoms, facts, or events in a systematic and accurate manner, regarding the characteristics of a particular population or area of ​​25 people with a total sampling technique. Collecting data in this study used a type of questionnaire instrument that contained the characteristics of the respondents and the behavior of using personal protective equipment (PPE). Results: The results of this study show an overview of the use of personal protective equipment (PPE) by nurses in the APARMA Unipdu Covid-19 Special Room in the use of head coverings, surgical or N95 masks, face shields, surgical gowns and isolation gowns, aprons, gloves and shields shoe. Conclusion: in general, nurses at the Aparma Healthy Home use personal protective equipment in accordance with the regulations of the Ministry of Health.